Exploring Comprehensive Approaches to Employee Health and Happiness - Hartanto, Oki (Advances in Human Resource Management Research, 2024)
Purpose: This study explores comprehensive approaches to employee health and happiness within the organizational context. It aims to understand the factors influencing employee well-being and their impact on organizational effectiveness. Research Design and Methodology: The research employs a qualitative literature review methodology, involving systematic analysis and interpretation of existing studies. This approach includes data collection from various academic sources, thematic analysis, and narrative synthesis to identify key themes and patterns in literature. Findings and Discussion: The findings indicate that employee health and happiness are influenced by multiple factors such as job characteristics, social support networks, organizational policies, and leadership styles. Comprehensive wellness programs, mental health support, and stress management strategies are shown to enhance employee well-being. Additionally, supportive organizational cultures and transformational leadership contribute to positive work environments, improving employee health and happiness. Implications: The study emphasizes the importance of holistic approaches in promoting employee well-being. Organizations are advised to adopt evidence-based policies and practices that support work-life balance, employee development, and performance recognition. Further research is needed to evaluate the effectiveness of wellness interventions across diverse organizational contexts to ensure their sustainability and long-term impact.